2016
DOI: 10.1097/md.0000000000005393
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting the likelihood of lymph node metastasis in early gastric signet ring cell carcinoma

Abstract: Treatment algorithm has not been established for early gastric cancer with signet ring cell carcinoma (SRC), which has a reported low rate of lymph node metastasis (LNM) similar to differentiated cancer. A cohort of 256 patients with early gastric SRC at our center between January 2002 and December 2015 were retrospectively reviewed. Multivariate logistic regression analysis was used to determine the independent factors of LNM. A nomogram for predicting LNM was constructed and internally validated. Additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Wei et al 18 included the clinical information from 1,030 patients with locally advanced (stage II and stage III) GSRC between 2004 and 2012, and constructed CSS prognostic nomogram based on age, sex, race, marital status, stage, registy, lymph node, location, tumor size, radiotherapy and chemotherapy, and found that patients who received postoperative radiotherapy had a better prognosis than patients who underwent surgery alone. Guo et al 17 collected 256 early-stage GSRC between January 2002 and December 2015, constructed a nomogram predicting lymph node metastasis (LNM) and performed external validation using a database of 1,273 patients from Cancer Institute Ariake Hospital in Tokyo. Lin et al 29 collected patients with gastric adenocarcinoma containing GSRC and constructed a gastric adenocarcinoma-specific survival (GCSS) prognosis nomogram based on age, race, grade, TN stage, pathological type and tumor size, which can provide relatively accurate survival predictions for patients with operable gastric adenocarcinoma (GA) after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al 18 included the clinical information from 1,030 patients with locally advanced (stage II and stage III) GSRC between 2004 and 2012, and constructed CSS prognostic nomogram based on age, sex, race, marital status, stage, registy, lymph node, location, tumor size, radiotherapy and chemotherapy, and found that patients who received postoperative radiotherapy had a better prognosis than patients who underwent surgery alone. Guo et al 17 collected 256 early-stage GSRC between January 2002 and December 2015, constructed a nomogram predicting lymph node metastasis (LNM) and performed external validation using a database of 1,273 patients from Cancer Institute Ariake Hospital in Tokyo. Lin et al 29 collected patients with gastric adenocarcinoma containing GSRC and constructed a gastric adenocarcinoma-specific survival (GCSS) prognosis nomogram based on age, race, grade, TN stage, pathological type and tumor size, which can provide relatively accurate survival predictions for patients with operable gastric adenocarcinoma (GA) after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram has been constructed in GSRC and have been validated as valid and correct. 17,18 However, the population selection of the above studies were relatively limited. In this context, we used the Surveillance, Epidemiology, and End Results (SEER) database to analyze the clinicopathological features and prognostic factors of OS and CSS in patients with GSRC, and developed and verified 3-year and 5-year OS and CSS prognostic nomograms of patients with GSRC.…”
Section: Introductionmentioning
confidence: 99%
“…All the included studies were of low risk of bias with respect to the domain of participants and outcome, 19 (46.34%) studies had low risk of bias in predictors ( 32 , 34 , 37 , 38 , 40 , 42 , 44 , 54 56 , 60 , 62 , 63 , 66 71 ), 22 (53.66%) had unclear risk of bias due to that the prediction assessment was performed in the know of outcome data ( 33 , 35 , 36 , 39 , 41 , 43 , 45 53 , 57 59 , 61 , 64 , 65 , 72 ). As for the domain of analysis, the risk of bias in 16 studies was considered high ( 33 , 35 , 41 , 43 , 47 , 50 , 51 , 53 , 58 , 59 , 61 , 63 , 65 , 68 , 70 , 71 ), and the reasons were that (1): Insufficient sample size.…”
Section: Resultsmentioning
confidence: 99%
“…However, two issues should be addressed for undifferentiated EGC. First, signet ring cell carcinoma (SRCC), which is classified as undifferentiated EGC, has a lower risk of LNM than purely undifferentiated EGC and should be treated differently . One study found that early SRCC (13.1% [26/198]) had a lower risk of LNM than undifferentiated carcinomas (23.8% [124/522]) and even a risk of LNM that was similar to differentiated carcinomas (9.8% [34/347]), which was also confirmed by Lee et al's study .…”
Section: Endoscopic Resection Indications For Egcmentioning
confidence: 87%